Cortinarius hesleri (Basidiomycota, Agaricales, Cortinariaceae), first record for Mexico - Hernández Del Valle, Juan Francisco; Sánchez Flores, Marcos; de la Fuente, Javier Isaac; Medrano Zapata, Eduardo Manolo; García Jiménez, Jesús (Instituto de Ecología, A.C., 2022)
Background and Aims: The genus Cortinarius consists of ectomycorrhizal fungi, characterized by a partial veil, forming an arachnoid "curtain", spore print rust brown to orange-orange brown, and basidiospores rough, wrinkled or warty and without apical pore. Cortinarius hesleri is placed in the subgenus Telamonia, and can be recognized mainly by its basidiomas with colors from red to orange tones. Fungal inventories facilitate the recognition of species for a specific geographic area. The aim of this work is to present C. hesleri as a first record for Mexico. Methods: The specimens were collected in Quercus forests from the municipality of Victoria, in the state of Tamaulipas. A macro- and micromorphological description of the species was prepared, as well as plates with macroscopic photographs in situ and photographs and illustrations of the microscopic structures, for subsequent analysis and taxonomic identification with the corresponding specialized literature. The studied specimens were deposited in the mycological herbarium José Castillo Tovar from the Instituto Tecnológico de Ciudad Victoria. Key results: The studied specimens meet the characteristics of the original description of the species, as well as those of the habitat to which it is associated and in which it is distributed. Cortinarius hesleri is described for the first time for Mexico. This species is characterized by its orange basidiomata, ornate ellipsoid spores of (7-)8-10(-12) × (5-)5.5-7 µm and its association with plant species from the Quercus-Pinus mixed forest. Conclusions: Cortinarius hesleri is widely distributed from the northern and eastern part of the United States of America, reaching its southernmost distribution known so far in the state of Tamaulipas, in Mexico. Due to its potential ectomycorrhizal association with forest species of the genera Quercus, Pinus and Carya, C. hesleri could be found distributed with these plant species in other sites in the northeast and the eastern part of Mexico.